HUBUNGAN ASUPAN GIZI DENGAN INDEKS MASSA TUBUH (IMT) DAN KADAR HEMOGLOBIN NARAPIDANA UMUM WANITA SEMARANG - Puji Sri Rahayunigtyas; Dina Rahayuning Pangestuti; M . Zen Rahfiludin (Jurnal Kesehatan Masyarakat (Undip), 2018)
The prisoners  have the right to receive decent food service. The food must meet the balanced nutrition, in terms of both quality and quantity as well as feasible and safe for consumption in order to support the nutritional status and health status in order to improve the quality of human resources. The purpose of this research is to analyze the correlation of nutrient intake with Body Mass Index (BMI) and hemoglobin levels of common Women Prisoners Class IIA Semarang. The research method used in this research is explanatory research with cross-sectional design. The Sampling technique used was total sampling with a total sample of 52 female prisoners. The results showed that the average BMI was 23,32 kg/m2 ± 4,08, hemoglobin levels was 10,80 g/dl ± 1,55, total intake of energy: 1796,70 kkal ± 2484,80, protein was 70,10 g ± 29,90, vitamin A was 1361,50 µg ± 671,20, vitamin C was 124,40 mg ± 86,60, iron was 12,10 mg ± 3,16, folat acid was 283,40 µg ± 98,80. The results of the bivariate analysis showed that there was correlation total intake of energy (p < 0,001, r = 0,754), protein (p < 0,001, r = 1,000) and BMI, there was correlation total intake of energy (p < 0,001, r = 0,755), protein (p < 0,001, r = 0,970) and hemoglobin levels, there was no correlation total intake of vitamin A (p = 0,459, r = 0,105), vitamin C (p = 0,271, r = 0,156), iron (p = 0,166, r = 0,195), folic acid (p = 0,285, r = 0,151) and hemoglobin levels.